Bioenergetics David G. Nicholls, Stuart J. Ferguson, W.R. Miller. - Nicholls, David G.; Ferguson, Stuart J. (Stuart John) 1949- (Academic Press, Elsevier, 2013)
Extensively revised, the fourth edition of this highly successful book takes into account the many newly determined protein structures that provide molecular insight into chemiosmotic energy transduction, as well as reviewing the explosive advances in 'mitochondrial physiology'-the role of the mitochondria in the life and death of the cell. Covering mitochondria, bacteria and chloroplasts, the fourth edition of Bioenergetics provides a clear and comprehensive account of the chemiosmotic theory and its many applications. The figures have been carefully designed to be memorable and to convey the key functional and mechanistic information. Written for students and researchers alike, Bioenergetics is the most well-known, current and respected text on chemiosmotic theory and membrane bioenergetics available.